Olive cultivar and maturation process on the oviposition preference of Bactrocera oleae (Rossi) (Diptera: Tephritidae) - Malheiro, Ricardo (2018)
The olive fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae), is a key-pest in the main olives producing areas worldwide, and displays distinct preference to different olive cultivars. The present work intended to study oviposition preference towards three Portuguese cultivars (Cobrançosa, Madural, and Verdeal Transmontana) at different maturation indexes. Multiple oviposition bioassays (multiple-choice and no-choice) were conducted to assess cultivar preference. No-choice bioassays were conducted to assess the influence of different maturation indexes (MI 2; MI 3, and MI 4) in single cultivars. The longevity of olive fly adults according to the cultivar in which its larvae developed was also evaluated through survival assays.Cultivar and maturation are crucial aspects in olive fly preference. Field and laboratory assays revealed a preference towards cv. Verdeal Transmontana olives and a lower susceptibility to cv. Cobrançosa olives. A higher preference was observed for olives at MI 2 and MI 3. The slower maturation process in cv. Verdeal Transmontana (still green while the other cultivars are reddish or at black stage) seems to have an attractive effect on olive fly females, thus increasing its infestation levels. Olive fly adults from both sexes live longer if emerged from pupae developed from cv. Verdeal Transmontana fruits and live less if emerged from cv. Cobrançosa. Therefore, olive cultivar and maturation process are crucial aspects in olive fly preference, also influencing the longevity of adults.